PERAN PENDIDIKAN, PENGALAMAN, DAN INOVASI TERHADAP PRODUKTIVITAS USAHA KECIL MENENGAH - Mandala, Ardy Mandala; Raharja, Edy (Diponegoro Journal of Management, 2012)
ABSTRACT The research was motivated by the rapid growth of SMEs, but are not offset by significant productivity growth. By looking at existing problems, this study aimed to analyze the influence of the factor of education, the experience and the innovation on the productivity of small and medium businesses in the city of Semarang. This study aims to determine the factors that affect the productivity of small and medium businesses in the city of Semarang and can help small and medium business owners improve the factors that affect productivity positively. In this study population used is the Small and Medium Enterprises in the field of Fashion and Crafts batik in the city of Semarang. Population from this study gained from annual report Disperindag Semarang in 2011. The number of samples is determined based on the calculation of the Slovin formula with a tolerable error rate of 10%, then the number of samples obtained by 67 people from 200 people in population. Data analysis methods used in this study is a simple linear regression and Independent Samples T-Test, where the classical assumptions previously made ​​trial. The results showed that education and experience have a positive and significant effect on on the productivity variable. And there is a difference in productivity between SMEs with innovation in, and the SMEs without innovation in it. Writers advice to the government is to improve the common welfare and continuously increasing the interest to learn of SMEs`s owner by increasing the need of training.